Conditions of ›Real‹ Dialogues in Cultural Contacts (KULT_online, 2012)
The anthology Dialogische Beziehungen und Kulturen des Dialogs (Dialogic Relations and Cultures of Dialogue) is dedicated to the Austrian comparatist Fridrun Rinner, and was published on the occasion of her 65th birthday. It is not meant to be a commemorative publication, however, since the authors were not asked to write homage to their teacher and mentor (cf. p. 20). Instead, the authors and editors want to introduce the concept of dialogue back into the discussion – but under new, critical perspective. Thus, in the face of political framework the importance of the power factor for an investigation of trans- or intercultural dialogues emerges. This is shown as successfully by the theoretical contribution on the concept of dialogue, as by the three literary case studies on dialogues between France and Germany or Austria, respectively.